KEPRAKTISAN ENSIKLOPEDIA FAMILI FABACEAE KEBUN RAYA BANUA UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Nurviati, Sri; Zaini, Muhammad; Rezeki, Amalia (Universitas Lancang Kuning, 2023)
Research development is research that aims to improve research that has been done before to improve the quality of learning materials. An encyclopedia is a type of learning material in the form of a book (a series of books) which compiles descriptions of various matters and is arranged alphabetically or according to the scientific environment. Generally, encyclopedias combine text with collaborative images in such a way that it is interesting. This study aims to describe the validity of the content, the practicality of the contents and the expectations and effectiveness of the expectations of the Fabaceae family encyclopedia. The research method used is the Tessmer design, which consists of: 1) self evaluation; 2) expert review; 3) one-to-one evaluation; 4) small group evaluations; The validation subjects included three experts, the individual test subjects were four students who were taking the phanerogamae course and the small group test subjects were four students who were taking the phanerogamae course. Data were obtained from research instruments on content validity, practicality of content, practicality of expectations, and effectiveness of expectations. The results of the study showed: 1) The validity of the contents of the encyclopedia was categorized as valid, namely 3.80, 2) the practicality of the contents was categorized as good, namely 3.82, and the practicality of expectations was categorized as very good, namely 85.71%, 3) The effectiveness of the expectations was categorized as very good, namely 88, 89%, so as to be able to train critical thinking skills. The Encyclopedia of the Fabaceae Family of the Banua Botanical Garden was declared valid including content, language and design. Practical because it has appeal and is easy to use so it gives a positive response (very good). Effective because it can train students' critical thinking skills.